PENGARUH MODEL PEMBELAJARAN READING WORKSHOP TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SD NEGERI 50 EREBULU SINJAI - Rochmanah; Khaltsum, Ummu; Saeful, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Reading Workshop learning model on the reading comprehension skills of fourth-grade students at SD Negeri 50 Erebulu Sinjai. The research employed a quasi-experimental design using a pretest- posttest control group design. The study population consisted of all fourth-grade students of SD Negeri 50 Erebulu Sinjai. The sample was selected using a total sampling technique, in which all members of the population were involved in the study. Data were collected through essay tests administered before and after the treatment to measure students’ reading comprehension skills. The research procedure included administering a pretest, implementing the Reading Workshop model in the experimental class while the control class received conventional instruction, and conducting a posttest. Data were analyzed using descriptive statistics and hypothesis testing to examine the significance of differences between groups. The results showed that students’ reading comprehension skills improved after the implementation of the Reading Workshop model. The experimental class obtained a mean pretest score of 72.30 and a mean posttest score of 90.50, indicating a substantial improvement and achievement of learning mastery. Furthermore, the hypothesis test yielded a significance value of 0.001, which was lower than the significance level of 0.05 (0.001 < 0.05). Therefore, it can be concluded that the Reading Workshop learning model has a significant positive effect on the reading comprehension skills of fourth-grade students at SD Negeri 50 Erebulu Sinjai.